2018
DOI: 10.1186/s13013-018-0151-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-structural misalignments of body posture in the sagittal plane

Abstract: BackgroundThe physiological sagittal spinal curvature represents a typical feature of good body posture in the sagittal plane. The cervical and the lumbar spine are curved anteriorly (lordosis), while the thoracic segment is curved posteriorly (kyphosis). The pelvis is inclined anteriorly, and the lower limbs’ joints remain in a neutral position. However, there are many deviations from the optimal body alignment.The aim of this paper is to present the most common types of non-structural misalignments of the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 21 publications
2
81
0
6
Order By: Relevance
“…Abnormal body posture is a term commonly used in clinical practice to describe the relationships between different parts of the body in the sagittal, frontal, and horizontal planes that may be considered defective, non-ergonomic, and likely to affect the functioning of internal organs. It is believed that incorrect posture may place an increased strain on the soft tissues and skeletal system, and interfere with the body's balance [53]. The work of Manshadi et al [54], studying 160 women with urinary incontinence, showed a statistically significant difference in the asymmetry of the pelvis in a standing position, compared to healthy women.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal body posture is a term commonly used in clinical practice to describe the relationships between different parts of the body in the sagittal, frontal, and horizontal planes that may be considered defective, non-ergonomic, and likely to affect the functioning of internal organs. It is believed that incorrect posture may place an increased strain on the soft tissues and skeletal system, and interfere with the body's balance [53]. The work of Manshadi et al [54], studying 160 women with urinary incontinence, showed a statistically significant difference in the asymmetry of the pelvis in a standing position, compared to healthy women.…”
Section: Discussionmentioning
confidence: 99%
“…Viewed on the sagittal plane, the most prevalent functional postural disorders of the spinal column include: kyphosis, lordosis, kypho-lordosis, and flat back (Кosinac, 2008;Stoliński, Tyrakowski, Kozinoga, & Kotwicki, 2018). Less prevalent postural disorders which also occur in the sagittal plane are the concave and rounded back (Živković, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The curve is often S-shaped or C-shaped. Structural alterations to the spine may lead to functional disturbances that, in turn, cause pain, inflammation, muscle weakness, nervous system stimuli disorders, and injuries [ 4 ]. Spine deviations are classified as “paramorphisms” and “dysmorphisms”.…”
Section: Introductionmentioning
confidence: 99%
“…The onset could be determined by several factors including muscle weakness due to low physical activity, inappropriate posture as well as improper transportation of school equipment [ 8 ]. Broadly, it consists of a combination of incorrect postural habits and muscle hypo/hyper-activity [ 4 ]. Posture is a widely studied matter, as is its interaction with Kinesio Taping (KT) methods.…”
Section: Introductionmentioning
confidence: 99%